How to Grow an Invoicing Currency: Micro Evidence from Argentina - Felipe Benguria; Dennis Novy (CESifo GmbH, 2025)
How can a currency achieve more widespread international use? We study the internationalization of the Chinese renminbi (RMB) through the lens of a unique policy experiment in Argentina. In 2023, amid a severe dollar shortage, Argentina expanded a currency swap line with the People's Bank of China. Within the next few months, the share of imports from China invoiced in RMB surged rapidly to nearly 50% - displacing the US dollar, which had previously accounted for virtually all invoicing. Following the presidential election of late 2023, as macroeconomic policies changed and the dollar shortage eased, invoicing in RMB declined. We explore the mechanisms behind this aggregate pattern, using rich firm-level data on imports, bank-firm loan relationships, and bank balance sheets. Our results indicate that banks played a key role, in line with the dollar shortage narrative. First, firms with pre-existing relationships to banks with limited US dollar loans were more likely to switch to RMB. Second, firms borrowing from a Chinese state-owned bank were significantly more likely to use RMB. We also document firm-level spillovers, with RMB use for imports from China increasing the likelihood of RMB use for imports from other countries. Finally, we observe an effect on trade volumes. Firms switching to RMB saw increased total imports.
Keywords: E58; F14; F31; F33; G21; 330; banking; central bank; china; geoeconomics; invoicing; lending; renminbi; swap; trade; US dollar